Antiviral propierties of 5,5'-dithiobis-2-nitrobenzoic acid and bacitracin against T-tropic human immunodeficiency virus type 1 - Lara Villegas, Humberto Herman; Ixtepan Turrent, Liliana del Carmen; Garza Treviño, Elsa Nancy; Flores Teviño, Samantha M.; Borkow, Gadi; Rodríguez Padilla, Cristina (2011)
Bacitracin and the membrane-impermeant thiol reagent 5,5’-dithiobis-2-nitrobenzoic acid (DTNB) are agents known to inhibit protein disulfide isomerase (PDI), a cell-surface protein critical in HIV-1 entry therefore they are fusion inhibitors (FI). Here we investigated the possibility that Bacitracin and or DTNB might have other antiviral activities besides FI. By means of residual activity assays, we found that both compounds showed antiviral activity only to viruses T-tropic HIV-1 strain. Cell-based fusion assays showed inhibition on HeLa-CD4-LTR-b-gal (CD4) and HL2/3 cells treated with Bacitracin, and DTNB with the latest compound we observed fusion inhibition on both cells but strikingly in HL2/3 cells (expressing Env) indicating a possible activity on both, the cell membrane and the viral envelope. A time-of-addition experiment showed that both compounds act on HIV entry inhibition but DTNB also acts at late stages of the viral cycle. Lastly, we also found evidence of long-lasting host cell protection in vitro by DTNB, an important pharmacodynamic parameter for a topical microbicide against virus infection, hours after the extracellular drug was removed; this protection was not rendered by Bacitracin. These drugs proved to be leading compounds for further studies against HIV showing antiviral characteristics of interest